Kebijakan Pemerintah Daerah dalam Pengelolaan Pasar Tradisional di Kota Probolinggo - Pungky Praja Jatmika (Sawala : Jurnal Administrasi Negara, 2017)
Condition of traditional markets in the city of Probolinggo are considered uncomfortable for traders and consumers. Many parts of the physical buildings have damaged, lack of trash, sewage that has been closed, lack of lighting and the number of traders who are selling in the hall because they do not get stall. Vehicles parking around the market has also resulted in traffic congestion as well as vehicles belonging to traders and shoppers that coming / leaving the market. The markets condition as illustrated above, especially in pasar Baru market of Probolinggo city need to get more attention from multiple parties especially market stakeholders and specially from local government as manager. Although local governments have made efforts to empower pasar Baru as a competitive traditional market, the results have not been able to resolve the real problems. This research is qualitative research with fenomenological approach as it is suitable with social characteristics of traders and traditional market visitors. This research found that the local government of Probolinggo city still need to increase its attention in the improvement of pasar Baru management. These attentions should consider (1) the urgency to increase the cleanliness of the market environment, (2) the urgency of parking rearrangement to overcome the congestion, (3) the urgency of physical revitalization building so that the physical appearance of the building as a modern market, (4) the urgency of revitalization of comprehensive market layout architecture